2011
DOI: 10.5897/ajpp11.593
|View full text |Cite
|
Sign up to set email alerts
|

Enlisting the scientifically unnoticed medicinal plants of Pakistan as a source of novel therapeutic agents showing anti-venom activity

Abstract: Snake bite envenoming is a global occupational hazard and most of the people of the world trust in traditional medicine for snake poisoning. The present review elaborates scientifically un-investigated/ ignored medicinal plants of Pakistan showing chemical constituents of natural origin with possible mechanisms showing anti-venom activity. This review enlists 35 plants with their families, distribution in Pakistan, parts used traditionally for snake bite treatment and various active principles present in them.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Instead, the combined action of multiple active constituents present in the plants acts synergistically on different target structures such as receptors and enzymes. These chemical constituents are often referred to as 'multifunctional' due to their ability to exhibit more than one pharmacological or biochemical property [45,46,47,48] . Earlier studies on the phytochemical screening of Annona senegalensis have reported the presence of diverse secondary metabolites, including tannins [49] , flavonoids [49] , saponins [50] , glycosides [51] , and alkaloids [52] .…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the combined action of multiple active constituents present in the plants acts synergistically on different target structures such as receptors and enzymes. These chemical constituents are often referred to as 'multifunctional' due to their ability to exhibit more than one pharmacological or biochemical property [45,46,47,48] . Earlier studies on the phytochemical screening of Annona senegalensis have reported the presence of diverse secondary metabolites, including tannins [49] , flavonoids [49] , saponins [50] , glycosides [51] , and alkaloids [52] .…”
Section: Discussionmentioning
confidence: 99%
“…Artemisia is the other important member of this family, considered to comprise >500 medicinal species in the world ( Martín et al, 2003 ; Bisht et al, 2021 ). Traditionally, the members of Artemisia have been used to treat several diseases like hepatitis, cancer, inflammation, DM, and infections caused by microorganisms ( Asad et al, 2011 ). The discovery of artemisinin, which resulted in the 2015 Nobel Prize in Physiology or Medicine, has revolutionized the treatment of malaria worldwide ( Panda and Luyten, 2018 ).…”
Section: Asteraceae: the Largest Family With Diverse Medicinal Proper...mentioning
confidence: 99%